RATES OF EXUDATIVE RECURRENCE FOR EYES WITH INACTIVATED WET AGE-RELATED MACULAR DEGENERATION ON 12-WEEK INTERVAL DOSING WITH BEVACIZUMAB THERAPY. Issue 4 (April 2020) - Hwang, Richard Y.; Santos, Daniella; Oliver, Scott C. N.
Abstract : Purpose: To determine the recurrence rate of exudative age-related macular degeneration (wet AMD) in patients on 12-week dosing interval anti–vascular endothelial growth factor (anti-VEGF) bevacizumab therapy. Methods: A retrospective chart review was performed on wet AMD patients treated with anti-VEGF therapy using a "treat-and-extend" methodology at one physician's practice site over 2 years (2012–2014). Charts were evaluated for visual acuity, anti-VEGF agent used, treatment interval, duration of treatment, trials off of anti-VEGF therapy, evidence of exudation, and wet AMD recurrence characteristics. Results: Three hundred and twenty-one wet AMD patients were treated. Fifty-seven eyes were without active exudation by clinical examination or optical coherence tomography (OCT) and were maintained on repeating 12-week interval suppressive anti-VEGF therapy. Sixteen percent (8/49) showed exudation recurrence with an average 10% cumulative recurrence rate per year for eyes on bevacizumab. Eight eyes without active exudation were discontinued off of bevacizumab therapy. Sixty-three percent (5/8) demonstrated recurrence on average 4 months after stopping therapy. Conclusion: The findings in this study suggest that if a patient can be extended to 12-week interval bevacizumab therapy, there is on average a 10% chance of recurrence with each successive year. If anti-VEGF therapy is discontinued in these patients, there is an increased chance of recurrence by 4 months. Abstract : This retrospective chart review investigated the recurrence rate of wet age-related macular degeneration in patients who were on 12-week dosing interval anti–vascular endothelial growth factor bevacizumab therapy.